Prediction of All-Cause Mortality Based on the Direct Measurement of Intrathoracic Impedance. (January 2016) - Zile, Michael R.; Sharma, Vinod; Johnson, James W.; Warman, Eduardo N.; Baicu, Catalin F.; Bennett, Tom D.
Abstract : Background—: Intrathoracic impedance-derived OptiVol fluid index calculated using implanted devices has been shown to predict mortality; direct measurements of impedance have not been examined. We hypothesized that baseline measured impedance predicts all-cause mortality; changes in measured impedance result in a change in the predicted mortality; and the prognostic value of measured impedance is additive to the calculated OptiVol fluid index. Methods and Results—: A retrospective analysis of 146 238 patients within the Medtronic CareLink database with implanted devices was performed. Baseline measured impedance was determined using daily values averaged from month 6 to 9 after implant and were used to divide patients into tertiles: group L=low impedance, ⩽65 ohms; group M=medium impedance, 66 to 72 ohms; group H=high impedance, ≥73 ohms. Change in measured impedance was determined from values averaged from month 9 to 12 post implant compared with the 6- to 9-month values. OptiVol fluid index was calculated using published methods. All-cause mortality was assessed beginning 9 months post implant; changes in mortality was assessed beginning 12 months post implant. Baseline measured impedance predicted all-cause mortality; 5-year mortality for group L was 41%, M was 29%, and H was 25%, P <0.001 among all groups. Changes in measured impedance resulted in a change in the predicted mortality; the prognostic value of measured impedance was additive to the OptiVol fluid index. Conclusions—: Direct measurements of intrathoracic impedance using an implanted device can be used to stratify patients at varying mortality risk.